Analysis of CSR’s Impact on Consumer Behaviour in British Alcohol Industry - GONG, Fan (2018)
Recently, CSR has been raising high attention by the organizations and the public that researchers have started to find the whether it will have impact on consumers’ behavior. However, it remains the conflicts of interests in the high-risk industry where the companies will face severe problems in society. The social issues caused by alcohol production and irresponsible alcohol drinking are strict in UK and how the alcohol companies behave under this condition may have influence on the consumers. Therefore, this study aims to find out the effect of company’s CSR initiatives on consumers’ purchase intent through several aspects, including consumer awareness, consumer attribution, consumer attitude and consumer-company identification with the moderator effect of SRCB (socially responsible consumer behavior). By means of distributing questionnaires to nearly 200 people who used to visit, study or live in the UK for a period of time with the experience of buying and drinking alcohol, the study examined the participants’ SRCB level and how they will react to the top alcohol company Diageo’s CSR activities through their awareness, attribution, attitude, identification and the final purchasing desire. It has been found that consumer awareness and consumer attributions have no direct effect on consumers’ purchase intent as a result of the strong impact from SRCB. While the consumer attitude and consumer-company identification can generate a positive influence on the consumers’ purchasing decision and SRCB has been suggested to strength this effect under the high SRCB level conditions. The limitations could be the narrow investigation scope and the deficiency of factors to explain this relationship. Further studies are recommended to offer deep researches in the CSR effect on the company evaluation, consumer loyalty and other related aspects with a larger sample size within wider areas.